Effectiveness of Factor XIII Infusion in Treatment of Refractory Ureteral Leakage after Kidney Transplantation - Ryoichi Maenosono; Tomohisa Matsunaga; Hajime Hirano; Hayahito Nomi; Shunri Taniguchi; Yuya Fujiwara; Koichiro Minami; Hirofumi Uehara; Teruo Inamoto; Haruhito Azuma (Case Reports in Transplantation)
Despite the evolution of transplantation techniques, urological complications are common and result in loss of graft. We report the case of a 57-year-old man who developed continuous urine leakage despite pyeloureteral neoanastomosis and stenting after kidney transplantation from his dizygotic twin. Suspecting ureteral leakage, we performed pyeloureteral neoanastomosis using his native right ureter and a ureteral stent 5 days after the kidney transplant. However, urine leakage continued for several days. Because the plasma factor XIII level decreased to 48%, we administered factor XIII products (Fibrogammin P; CSL Behring, King of Prussia, PA) after the surgery. Although its utility and safety in patients with renal failure and/or transplantation are unclear, urine leakage stopped after the infusion of fibrogammin without any side effects. This is the first case report of the use of factor XIII for refractory urine leakage after kidney transplantation. Although further studies are needed, administration of factor XIII products could be one option for refractory urine leakage after transplantation.